STOCHASTICAL SIMULATION ON FLIGHT DEMAND IN FRACTIONAL AIRCRAFT OWNERSHIP'S MANAGEMENT - (NIM : 10108063) ; Pembimbing 1 : Dr. Novriana Sumarti; Pembimbing 2 : Dr. Rieske Hadianti, SHANNY
Rapid industrial growth led to increase mobility of people to go to other cities for business or vacation by aircraft. The need of secure flight schedule for business inspires the concept of Fractional Aircraft Ownership. Fractional Aircraft Ownership is a concept of sharing of flying hours on an aircraft based on shares held. Shareholders or owners of the share would be easy to travel by plane whenever they need privately and to fly to cities indicated in the FAO's management contract. As a result, the flight demands is stochastic. In this final project will be discussed how to simulate the demands that are stochastic, based on several assumptions that apply to Fractional Aircraft Ownership. The flight demands is generated based on two common distribution. The results of these simulations are used for optimization process in Fractional Aircraft Ownerships management, for example in determining the optimal number of aircraft must be owned by FAOs management.